نظام التوریق كمصدر من مصادر التمویل في الاقتصاد الحدیث دراسة وصفیة تحلیلیة - السبوسي سعید سیف (Finance and Business Economies Review, 2018)
The securitization system through countries that it regards as a source of financing in the modern economy, as well as financing through property rights through the state budget, finance in securities, self-financing through retained earnings, reserves, depreciation or loan financing, plays an important economic role in Drive economic growth and development forward. It creates an added value in encouraging the associated projects to specialize, using their competitive advantage. The securitization system requires the separation of financing, construction, service and risk. Each project is specialized in one of these aspects. At the state level.